Towards eradicating poverty in Malaysia: leveraging on MyMosqueNet2Cloud collaborative system - Hamid, Habiba; Khairuddin, Nur Dini; Ahmad Dahlan, Abdul Rahman; Ahmad H.Osman, Rahmah (2013)
Poverty alleviation is amongst the central goals of the Malaysian Government which they want to achieve with the aid of policies and programs such as the new economic policy and national economic plan. Despite this effort, 40% of household in the country hitherto struggle with a monthly take-home less than RM2, 300. Consequently, an effective strategy should be adopted to reduce the disparity of economic status between ethnics as well as rural and urban area in the country. In a bid to augment the Government effort, this paper proposes a conceptual collaborative IT system anchored on (a) Quadruple Helix Model (QHM), where a country's economic structure lies on four actors namely: government, industry, academia and citizen; (b) “Whole-of-Government” (WoG) approach which demand for a collaborative and co-operative arrangement of open consultation, open data, shared knowledge, consolidation of shared services and enhanced horizontal application across government agencies; and (c) citizen-centric Network-of-Mosques (NoM) – all geared towards achieving a higher quality of life for poor families in Malaysia. This System will expand the reach of the eKasih database which is proposed to be value-added by the Department of Islamic Development Malaysia (JAKIM) by capturing detailed information of the poor through NoM. The expected outcome is an enhanced quality of life for poor families in the country.